Gastrocnemius injuries in professional baseball players: An epidemiological study - Hultman, K.; Szukics, P. F.; Grzenda, A.; Curriero, F. C.; Cohen, S. B. (The American Journal of Sports Medicine, 2020)
Background: Gastrocnemius injuries are a common lower extremity injury in elite baseball players. There are no current epidemiological studies focused on gastrocnemius injuries in professional baseball players that provide information on the timing, distribution, and characteristics of such injuries.